Impact of periodontal status on oral health-related quality of life in patients with and without type 2 diabetes. Issue 5 (May 2015) - Irani, F.C.; Wassall, R.R.; Preshaw, P.M.
Abstract: Objectives: To investigate the impact of periodontal status on oral health-related quality of life (OHRQoL) in patients with and without type 2 diabetes mellitus (T2DM). Methods: 61 patients with T2DM and 74 non-diabetic patients matched for age, gender and periodontal status (health, gingivitis, chronic periodontitis) were recruited. The oral health impact profile (OHIP)-49 was self-completed by all participants at baseline and by the patients with periodontitis at 3 months and 6 months after non-surgical periodontal therapy. Results: There were no significant differences in the overall OHIP-49 summary scores between patients with T2DM (median; interquartile range; 37.0; 19.5–61.0) and without T2DM (30.4; 16.8–51.0) ( p  > 0.05). Among non-diabetic patients, there were significantly higher OHIP-49 scores (indicating poorer OHRQoL) in patients with gingivitis (41.0; 19.7–75.7) and periodontitis (33.0; 19.9–52.5) compared to patients who were periodontally healthy (11.1; 7.1–34.5) ( p  < 0.05), though such an effect was not observed in the patients with diabetes. In the non-diabetic patients with periodontitis, statistically significant reductions in OHIP-49 scores were noted in the psychological discomfort and psychological disability domains following periodontal treatment, indicating an improvement in OHRQoL. In contrast, there were no statistically significant changes in OHIP-49 scores following periodontal treatment in the patients with diabetes. Conclusion: T2DM does not impact on overall OHRQoL as measured by OHIP-49. Chronic periodontitis and gingivitis were associated with poorer OHRQoL in non-diabetic patients, with evidence of improvements following periodontal treatment, but no such effects were observed in patients with diabetes. Clinical significance: Gingivitis and periodontitis are associated with reduced OHRQoL compared to periodontal health in non-diabetic patients, with improvements following treatment of periodontitis. No impact of type 2 diabetes on OHRQoL was noted; this may be related to the burden of chronic disease (diabetes) minimising the impact of oral health issues on OHRQoL.